Comparison of Values the Professional of Nurses Who Are and Do Not Take Graduate Education - Eşe Yelekçi; Adalet Koca Kutlu (Association of Nurse Managers, 2020)
INTRODUCTION: This study made to compare the professional values of nurses who are and do not take graduate education. METHODS: Universe of the study that is a descriptive and cross-sectional was consisted of nurses working at a Training and Research Hospital. 308 nurses who accepted to participate in the study formed the sample of the study. The data of the study were collected by Personal Information Form and Professional Values of Nurses Scale. RESULTS: Nurses who are postgraduate education; 62.5% of them under the age of 30, 70.3% female, 65.6% single, 76.6% of less than 10 years it works, 71.9% work that as clinic nurses, 60.9% were found to receive education about professionalism. 54.5% of non-graduate nurses were over 30 years of age, 80.7% were women, 57.8% were married, 64.7% were bachelors, 54.5% were under 10 years. 83.6% worked as a clinic nurse and 84.4% was found to receive education about professionalism. In the study, it was determined that the mean and sub-dimensions of the nurses were higher and the difference was statistically significant. Besides, it was found that the mean scores of the nurses who had 10 years or less professional experience, who worked as ICU nurses and those who received professionalism training were higher and meaningful (p<.05). DISCUSSION AND CONCLUSION: It was found that the nurses who received postgraduate education were more higher mean of the Scale. Education should be considered in the formation of professional values in nursing.